2011
DOI: 10.1007/s00432-011-1121-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of PDCD4 expression is an independent predictor of poor prognosis in human renal cell carcinoma patients

Abstract: PDCD4 expression strongly correlated to RCC stage, tumor grade, tumor metastasis and tumor-related death. PDCD4 expression was also appears to be a marker in RCC prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Moreover, Li et al observed that PDCD4 expression was found to be significantly associated with RCC metastasis, tumor, T-stage and tumor grade. Furthermore, decreased PDCD4 expression proved to be an independent prognostic marker for overall survival in addition to the presence of tumor metastasis and high tumor grade, and mean overall survival was significantly decreased in the low PDCD4 group compared to the high PDCD4 group [31]. All these findings demonstrate that PDCD4 is potentially not only a tumor suppressor gene, but also an invasion inhibitor in RCC.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, Li et al observed that PDCD4 expression was found to be significantly associated with RCC metastasis, tumor, T-stage and tumor grade. Furthermore, decreased PDCD4 expression proved to be an independent prognostic marker for overall survival in addition to the presence of tumor metastasis and high tumor grade, and mean overall survival was significantly decreased in the low PDCD4 group compared to the high PDCD4 group [31]. All these findings demonstrate that PDCD4 is potentially not only a tumor suppressor gene, but also an invasion inhibitor in RCC.…”
Section: Discussionmentioning
confidence: 82%
“…1A shows reduced levels of PDCD4 in both these renal carcinoma cells as compared to normal renal proximal tubular epithelial cell HK2 (Supplementary Fig. S1A) [33]. To test the role of miR-21 in targeting PDCD4, we used a reporter plasmid containing 3′UTR of PDCD4 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Also, its role in invasion of several solid tumors has been reported [21, 34, 38, 39, 49, 6062]. More recently, decreased expression of PDCD4 has been reported in renal tumors [33]. Transcriptional and epigenetic regulations represent major mechanisms for PDCD4 expression [6365].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of PDCD4 is often suppressed in tumors and has been associated with poor survival outcomes [65][66][67][68]. A negative regulator of PDCD4 in tumorigenesis is miR-21, a micro-RNA that has also been widely implicated in tumor progression and is associated with poor prognosis in many cancers including, but not limited to lung cancers, breast cancers, gastric cancers, renal cell carcinomas, and glioblastomas [69][70][71][72][73][74][75][76]. Tumor suppressing properties of PDCD4 have also been observed within a laboratory setting, as PDCD4 −/− mice develop B cell lymphomas and epidermistargeted expression of PDCD4 suppresses carcinogen-induced tumor development [77,78], while administration of PDCD4 to an activated K-Ras lung tumor model via aerosol delivery inhibited carcinogenesis [79].…”
Section: Pdcd4 and Eif4amentioning
confidence: 99%